Efficacy of Intravascular Therapeutic Hypothermia for Moderate to Severe Hypoxic–Ischemic Encephalopathy - Tomonori Kurimoto; Takuya Tokuhisa; Itaru Hayasaka; Tsuyoshi Yamamoto; Eiji Hirakawa; Hiroshi Ohashi; Masaya Kibe; Asataro Yara; Takatsugu Maeda; Masato Kamitomo; Satoshi Ibara (Children)
Background/Objectives: Hypoxic–ischemic encephalopathy (HIE), affecting 1.3–1.7/1000 live births, is treated with conventional therapeutic hypothermia (TH) but carries significant mortality and neurological impairment. Here, we compared intravascular cooling with extracorporeal membrane oxygenation (ECMO) and conventional TH in neonates with moderate to severe HIE. Methods: We retrospectively analyzed single-center neonates born in 2000–2022. Neonates with a 10 min Apgar score ≤ 3 or umbilical artery pH ≤ 6.7, along with persistent pulmonary hypertension of the newborn and an oxygenation index of ≥25 to <40, were divided into ECMO (n = 17) and conventional TH (n = 18) groups and administered the Kyoto Scale of Psychological Development at 18 months. Results: Neonatal and maternal characteristics were similar between the groups. A significantly higher proportion of the ECMO group (70.6% vs. 33.3%) achieved a developmental quotient ≥ 70. Conclusions: Intravascular cooling with ECMO may improve the neurodevelopmental outcomes of neonates with HIE, severe acidosis, and low Apgar scores.